2005
DOI: 10.1097/01.brs.0000184314.26543.7d
|View full text |Cite
|
Sign up to set email alerts
|

An Outcomes Analysis of the Treatment of Cervical Pseudarthrosis With Posterior Fusion

Abstract: This is the first study to our knowledge to use standardized outcome measures to assess clinical outcome in patients treated with posterior fusion for pseudarthrosis after anterior cervical discectomy and fusion. Patients and surgeons need to understand the potential for success with this revision procedure but also be aware of the relatively high rate of continued moderate to severe pain observed in this patient population even after a solid fusion is achieved. All of the patients in this study fused with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 34 publications
1
54
2
Order By: Relevance
“…This suggests that authors of studies 1,7,[15][16][17][18]24 using the cutoff value of 2 mm of interspinous motion have overestimated their fusion rate and could have missed the pseudarthrosis cases that had interspinous motions ranging from 1 to 2 mm. Some laboratory studies 10,13,25 have also suggested an inherent inaccuracy of interspinous motion analysis because, even with solid fusion, some motion can occur between spinous processes due to elastic deformation of bone and facet joints.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…This suggests that authors of studies 1,7,[15][16][17][18]24 using the cutoff value of 2 mm of interspinous motion have overestimated their fusion rate and could have missed the pseudarthrosis cases that had interspinous motions ranging from 1 to 2 mm. Some laboratory studies 10,13,25 have also suggested an inherent inaccuracy of interspinous motion analysis because, even with solid fusion, some motion can occur between spinous processes due to elastic deformation of bone and facet joints.…”
mentioning
confidence: 89%
“…Unfortunately, the measurement of motion on dynamic radiographs can be inaccurate and affected by the voluntary effort of the patient [10][11][12] , giving rise to questions regarding the amount of motion on dynamic radiographs that is compatible with pseudarthrosis 1,3 . Many reports [11][12][13][14][15][16][17][18] have described radiographic parameters indistinctly, including the degree of magnification used and how it was determined whether the dynamic motion on radiographs was inadequate. Furthermore, only a few authors 6,10,15 have related their criteria to surgical confirmation of anterior cervical fusion status.…”
mentioning
confidence: 99%
“…6,11,14,21,23,25,28,29 This large range in nonunion rates reflect variation in patient comorbidities, surgical indications, number of cervical spine levels fused, and the type of instrumentation and bone graft used. The introduction of lateral mass screw-rod fixation systems have biomechanically allowed a more rigid fixation for early bone fusions in the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…6,11,15,23,24,29,31,32,54 This large range in nonunion rates reflects variation in patient comorbidities, surgical indications, tobacco use, anterior/posterior constructs, number of cervical spine levels fused, and the type of instrumentation and bone graft used. 54 The introduction of lateral mass screw-rod fixation systems has biomechanically allowed a more rigid fixation for early bone fusions in the cervical spine.…”
Section: Discussionmentioning
confidence: 99%